The work of Imam Abd al-Qahir al-Jurjani in his book “Asrar al-Balagha” - a descriptive and analytical study of the similarity of jurisprudence, representation, and metaphor. - Sebkha , mokhtar (Journal of Social Sciences and Humanities, 2025)
The research is an objective attempt to consider the work of Imam Abdul Qaher Al-Jurjani in establishing the science of rhetoric in its rhetorical aspect through his book “Secrets of Rhetoric”, specifically three topics known to him; namely, simile, metaphor, and allegory, and the extent of the contribution made to building the edifice of this science and establishing it, and what distinguished - a scientific approach - in the matter? In parallel with the assumption in the subject, which is that Imam al-Jurjani collected the scattered and did nothing but improve, we will delve into the matter in research approaching description, as well as analysis and induction of the most important things that came in the Imam’s book regarding the subjects of the study, to arrive at some of the most important results: that the Imam has outlined for himself a comprehensive method of taste for much of what may have an effect in revealing secrets that have been deposited in the Book of the Lord of the Worlds, the guidance of all mankind, and there is no harm in the Imam’s actions here being enlightened by those who came before, so that he created a method for others to be guided; for in taking and giving there is life.